WARGA MUHAMMADIYAH DAN NU DI LAMONGAN MEMANDANG TRADISI TINGKEBAN - Siti Khuzaimah (Religi: Jurnal Studi Agama-agama, 2015)
The Tingkeban tradition serves as one of important rituals besides the wedding and thefuneral. The fact indicates the reverse phenomenon of the splitting tendency among theadherents of Muhammadiyah and NU in that the ritual bears as the social sphere ofthe people. In this regard, it is important to fi rstly understand how the Muhammadiyahand the NU adherents gave their response to the Tingkeban and its functionality. Thisresearch uses Talcott Parsons’ Structural Functionalism that covered four premises ofAGIL that includes adaptation (A), goal attainment (G), integration(I) and lattenpattern maintenance (L). This fi eld research includes data collecting by observation,documentation and interviews to the community leaders as well as covers a participantobservation using a qualitative approach on a descriptive-analytical data.The study shows that fi rst, people consider the Tingkeban as Hindhu tradition and itis a kind of novelty in Islam. In the Muhammadiyah’s view among Karangrejo people,there is an exception between the Tingkeban and some other local tradition. Both aretruth, in their views, with a little difference in the Tingkeban practice in Karangrejo.Secondly, the function of Tingkeban as action system can be describes as follows. (A)Adaptation deals with slametan, landang/rewang and social invitation, (G) GoalAttainment covers the ideal of rukun, harmonis, dan selamat, (I) integration dealswith the making of Procot cake as Tingkeban symbol and (L) latency refers to theGrace to God. The function of Tingkeban is an effort to accomplish the harmony andbalance in a ‘society’ system. This signifi es the Tingkeban signifi cance as the Dawaregulation in Karangrejo Karanggeneng Lamongan.